БОЛАШАҚ МАМАНДАРДЫҢ КƏСІБИ МƏДЕНИЕТТІЛІГІН ДАМЫТУ (Experimental biology, 2015)
In the article is discussed necessary put on accent on the forming and development of culture in future specialist as well as forming active action in the work and profecional creaty.
Keywords: profecional creaty